2017
DOI: 10.1007/s10661-017-6172-3
|View full text |Cite
|
Sign up to set email alerts
|

Industrial pollution and the management of river water quality: a model of Kelani River, Sri Lanka

Abstract: Water quality of the Kelani River has become a critical issue in Sri Lanka due to the high cost of maintaining drinking water standards and the market and non-market costs of deteriorating river ecosystem services. By integrating a catchment model with a river model of water quality, we developed a method to estimate the effect of pollution sources on ambient water quality. Using integrated model simulations, we estimate (1) the relative contribution from point (industrial and domestic) and non-point sources (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…At least four major municipalities within the Kelani basin discharge untreated or partially-treated sewage and domestic wastewater into the river [27,[54][55][56][57], leading to excessive accumulation of organic waste, which then increases the BOD [58]. Over 6000 industries directly discharge waste into river (Table 1) [9,31,39,59]. The average daily point-source discharge is estimated to be over 414,600 cm 3 , creating a biological oxygen demand in excess of 11,600 kg day −1 [59].…”
Section: Point-source Pollutionmentioning
confidence: 99%
See 2 more Smart Citations
“…At least four major municipalities within the Kelani basin discharge untreated or partially-treated sewage and domestic wastewater into the river [27,[54][55][56][57], leading to excessive accumulation of organic waste, which then increases the BOD [58]. Over 6000 industries directly discharge waste into river (Table 1) [9,31,39,59]. The average daily point-source discharge is estimated to be over 414,600 cm 3 , creating a biological oxygen demand in excess of 11,600 kg day −1 [59].…”
Section: Point-source Pollutionmentioning
confidence: 99%
“…Over 6000 industries directly discharge waste into river (Table 1) [9,31,39,59]. The average daily point-source discharge is estimated to be over 414,600 cm 3 , creating a biological oxygen demand in excess of 11,600 kg day −1 [59]. Although the focal environmental regulator of Sri Lanka, the Central Environmental Authority, identified these pollution sources decades ago, neither legal nor remedial actions have been taken thus far [31].…”
Section: Point-source Pollutionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an integrated model simulation on Kelani River pollution carried out by Gunawardena et al (2017), the estimated transfer coefficients revealed that industrial parks have a considerably higher impact across all identified zones in the river basin although these parks generally comply with existing effluent concentration standards. In a biomarker assessment study, Ruvinda and Pathiratne (2018) found neurotoxic, genotoxic and liver histopathological effects in the fish Nile tilapia, Oreochromis niloticus after short term laboratory exposure to the water samples from the confluence of Manikagara Ela and Maha Ela.…”
Section: Resultsmentioning
confidence: 99%
“…In the proposed 'multistakeholder strategy and action plan for management and conservation of the Kelani River basin 2016-2020', the importance of pollution impact assessments has been emphasised (Mallawatantri et al, 2016). A large number of industries including several export oriented industrial parks are located in close vicinity of Kelani River (Gunawardena et al, 2017). The industries located in these industrial zones/parks are required to treat their wastewater chemically in in-house treatment plants until specified national tolerance limits (Anonymous, 2008) are met.…”
Section: March 2020mentioning
confidence: 99%